Relationship of Hematological Indices with the Outcome of Dengue Infection - MALEEHA ZIA MUFTI; YASAR MEHMOOD YOUSAFZAI; MUHAMMAD ZEESHAN HAROON; RASHID ALI; SUNIA QASURIA KHAN; HAMZA JAVED (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Dengue infection poses a significant global health challenge, necessitating a comprehensive understanding of its hematological dynamics for effective clinical management. This study aimed to investigate the hematological parameters of dengue-infected patients, emphasizing platelet dynamics and their correlation with disease severity. Methodology: This longitudinal study, conducted at Ayub Teaching Hospital, spanned August 2022 to February 2023. Employing consecutive sampling, 146 dengue patients were enrolled after obtaining approval from the ASRB/IRB IPDM KMU. Patients of all ages and both genders were included, except those with known ITP, hematologic malignancy, or any chronic disease. Data collection encompassed demographic characteristics and clinical symptoms, gathered through a proforma after obtaining informed consent. Hematological parameters were meticulously assessed at defined intervals Data analysis was done using SPSS V.25 and Graph-Pad Prism software. A p value ≤ 0.05 was deemed statistically significant. Results: The mean age of participants was 38.58 ± 18.53 years. Thrombocytopenia classification revealed 50% mild, 32.9% moderate, and 17.1% severe cases at diagnosis, with 76.02% achieving normal platelet counts by the 10th day. Platelet counts and indices exhibited temporal normalization significantly quickly in a non-hospitalized group of patients, signifying recovery. Crucially, the platelet count at diagnosis was found to be a robust predictor for hospitalization, with lower counts correlating significantly with an increased likelihood of hospital admission on multivariate logistic regression [Exp(B) = 0.964, p<0.001]. Conclusions: We emphasize the predictive power of the platelet count at diagnosis for dengue severity. Trends, like the rapid normalization of platelet morphology and indices in non-hospitalized patients, provide valuable insights for clinicians, guiding more effective clinical decisions. Keywords: Dengue Virus, Dengue fever, Epidemiology, Disease severity, Clinical Outcomes